Relationship between choice overload effect and need for cognitive closure - Teo, Joan Zhi Min (2016)
Large choice sets were believed to be beneficial for both marketers and consumers. However, the current study aims to demonstrate otherwise through the choice overload effect and a potential moderating variable – need for cognitive closure (NFCC). Two-way ANOVA revealed greater perceived task difficulty in the extensive-choice condition, as well as higher enjoyment level for participants under no noise condition. Participants’ intention to purchase was influenced by an interaction effect between choice and noise conditions, where extensive-choice and noise condition had the highest ratings. In essence, while there was no significant empirical results in support for choice overload effect nor the demonstration of NFCC as a potential moderator, this study still presents itself as a meaningful contribution to existing literature.